The effect of participating in support groups on relocation stress syndrome in residents of a nursing home: A single-blind randomized clinical trial - Fatemeh Hosseinzadeh; Sahar Ghaderi; Sarieh Poortaghi; Reza Negarandeh (Tehran University of Medical Sciences, 2021)
Background & Aim: Relocation stress syndrome is one of the consequences of moving someone to a nursing home; it causes unbearable feelings of loneliness, anxiety, and depression. However, it can be prevented by conducting proper and timely nursing interventions. The present study aimed to examine the effect of participation in support groups on relocation stress syndrome in residents of nursing homes. Methods & Materials: In this single-blind randomized clinical trial, 32 elderly residents of Kahrizak nursing home were randomly assigned to control and intervention groups. The intervention included holding support groups. Demographic information questionnaires, the short form of Geriatric Depression Scale (15-GDS), Geriatric Anxiety Scale (GAS), and the short form of University of California, Los Angeles, UCLA loneliness scale (ULS-8) were used to collect data. The data were then analyzed using statistical tests in SPSS software version 16. Results: There was no statistically significant difference between the mean scores of loneliness, depression, and anxiety between the two groups in the pre-test (p> 0.05). The results of the ANCOVA test to compare the mean scores of loneliness, depression, and anxiety in the post-test with controlling pre-test scores revealed that the intervention was effective on depression (p<0.001) and anxiety (p= 0.003), but it had no effects on loneliness (p= 0.156). Conclusion: The development and implementation of support group programs for the elderly in a nursing home could improve the outcomes of relocation stress syndrome in terms of depression and anxiety. Nonetheless, it had no effects on the outcome of loneliness. Therefore, it is recommended to implement this intervention for the elderly in a nursing home if the cost-benefit analysis is positive.